Fatigue Acetabular Fracture after Lumbopelvic Instrumented Fusion in Elderly - Panagiotis Korovessis; Vasileios Tsekouras; Alkis Korovesis (Case Reports in Orthopedics)
Purpose. Only several cases of acetabular “fatigue”/insufficiency fractures have been reported in elderly patients with osteoporosis. However, fatigue acetabular fracture below lumbopelvic fixation has not been published. This review reports on the frequency and mechanisms of acetabular fatigue fractures in elderly individuals, including postmenopausal osteoporosis, and presents a case of an acetabular “fatigue” fracture in association with lumbopelvic fusion. Methods. We report on a 71-year-old postmenopausal woman who underwent in our department a L2-pelvis instrumented fusion for failed lumbar decompression and interbody fusion performed in another institution. For at least one year, the patient was receiving antiosteoporotic treatment (Alendronate plus Calcium and Vitamin D) and was fully ambulatory without limping. Eighteen months following our surgery, the patient sought again our department because of increasing pain in her right hip and limping without trauma. Results. The physical examination disclosed painful passive motion in her right hip. The roentgenograms and CT-scans disclosed a transverse acetabular fracture with radiolucencies around both iliac screw tips, particularly the right. Additionally, a severe compression fracture of the 12th thoracic vertebral body and upper endplate of the L2 vertebra was disclosed. We recommended open stabilization of the acetabulum and T12 and L2 vertebrae. Immediately before the planned surgeries, the patient had a serious heart infarct, and thus, surgeries were canceled by the patient’s cardiologist because of the high perioperative risk. The patient and relatives denied further surgeries because of the heart disease. In the final telephone call and CT and roentgenographic evaluation that went to us after request, there was an acetabular pseudarthrosis in the right hip without however associated complaints. Since surgery was not accepted, the patient was prescribed Denosumab injection therapy plus Vitamin and Calcium supplement. Conclusion. This case report emphasizes the significance of follow-up observation of elderly patients with postmenopausal osteoporosis following lumbopelvic fusions, for possible fatigue acetabular and vertebral fractures. The authors speculate that this extremely rare acetabular “fatigue”/insufficiency fracture should be the result of increased repetitive mechanical forces acting around the acetabulum in association with osteoporosis.